The Implementation of a Problem-Based Learning (PBL) Model Assisted by Wordwall Media in the IPAS Subject to Enhance Students' Learning Outcomes - Ariyani Ariyani; Nazurty Nazurty; Sukendro Sukendro (Postgraduate, University of Mataram, 2025)
The Problem Based Learning (PBL) instructional model is an approach used to address problems encountered in real-world activities. It is a learning model that also considers deep thinking styles and skillful problem formulation to help students gain an understanding of the main topics and key concepts. This study aims to evaluate the implementation of the Problem Based Learning (PBL) model, supported by Wordwall media, in improving the learning outcomes of fourth grade students in the IPAS subject at SD Negeri 1 Bayung Lencir. The research employed a Classroom Action Research (PTK) method over four cycles. The study involved 21 fourth grade students, and data were collected through tests, observations, interviews, and documentation. The results indicated a significant improvement in students’ learning outcomes from the pre-test to the post-test. Before the model was applied, only one student achieved mastery. After implementing the PBL model with Wordwall media, the number of students reaching mastery increased to 11 out of 12. The use of PBL and Wordwall media proved effective in enhancing student motivation and learning outcomes, as well as in supporting active student engagement in the learning process. The study recommends that teachers adopt a problem-based learning model supported by interactive media to further improve student learning outcomes